Paraconsistent Autonomous Mobile Robot Emmy III - Torres, Claudio Rodrigo (IOS Press, 2009)
This work presents some improvements regarding to the autonomous mobile robot Emmy based on Paraconsistent Annotated Evidential Logic ET. A discussion on navigation system is presented.
Keywords: Automation; paraconsistent logic; robotics; navigation system; logic controller